Advance Chemical Mechanical Polishing Technique for Gallium Nitride Substrate - Xuanyi Zhao; Shouzhi Wang; Lei Liu; Qiubo Li; Jiaoxian Yu; Guodong Wang; Chang Liang; Zhongxin Wang; Han Hao; Xiangang Xu; Lei Zhang (Advanced Materials Interfaces)
Abstract As the representative of substrate material, gallium nitride (GaN) has excellent mechanical properties and high thermal stability. Achieving high surface flatness is critical for subsequent epitaxial growth and device fabrication processes. Chemical mechanical polishing (CMP) technique of GaN is commonly one of the most effective ways to achieve atomically smooth surfaces. However, the current process is difficult to meet the needs of industrial development due to the characteristics of low material removal rate. Assisted enhanced CMP technique is deemed to possess significant potential due to its improved processing efficiency and surface topography quality. Herein, a variety of auxiliary enhanced CMP systems are designed and studied. In this review, recent advances both in conventional and assisted enhanced CMP of GaN are comprehensive presented, with a focus on their potential applications in various fields. The mechanism and design strategy of the process are discussed and summarized. The key issues in machining atomically flattened surface are outlined, and future strategies for sustainable development are also proposed. This review provides a novel perspective on GaN processing and offers more inspiration for future research to realize its development and commercial application.